Strategic Management - Richard Lynch (UK Pearson, 2015)
Strategic Management is one of the world's leading strategy textbooks. It covers all the major topics, particularly from a global perspective. It delivers comprehensive coverage of all the main elements of the subject in an easy-to-read style with extensive examples and a range of free support material that will help you learn actively and effectively.